Polishing composition

CN116848211BActive Publication Date: 2026-10-30FUJIMI INCORPORATED
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202280010432.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-01-18
Filing Date
2022-01-12
Publication Date
2026-10-30
Estimated Expiration
2042-01-12

AI Technical Summary

Technical Problem

硅晶圆中HLM的部分本身不被用于最终产品,但HLM赋予后的抛光工序(特别是预备研磨工序)中,若上述变质层未被适当研磨,则可能成为隆起并导致成品率降低必要以上的水平

Benefits of technology

[0017]此处公开的研磨用组合物的一个优选方式中,上述磨粒包含二氧化硅颗粒。使用二氧化硅颗粒作为磨粒的研磨中,可抑制研磨速率的降低,并更有效地发挥消除HLM周缘隆起的效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004341911650000211
    Figure BDA0004341911650000211
Patent Text Reader

Abstract

Provided is a polishing composition that can simultaneously inhibit a decrease in polishing rate and eliminate HLM peripheral bulging at a high level. A polishing composition for use in a preliminary polishing process of a silicon wafer is provided. The polishing composition comprises abrasive grains, an alkaline compound, a chelating agent, a surfactant, a nitrogen-containing water-soluble polymer, and water. The ratio (B / S) of the weight concentration (B) of the alkaline compound to the weight concentration (S) of the surfactant is 50 or greater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to polishing compositions. More specifically, it relates to polishing compositions for pre-polishing silicon wafers. This application claims priority to Japanese Patent Application No. 2021-5836, filed January 18, 2021, the entire contents of which are incorporated herein by reference. Background Technology

[0002] Silicon wafers used in the manufacture of semiconductor products typically undergo lapping (rough grinding) and polishing (precision grinding) processes to achieve a high-quality mirror finish. Typically, the polishing process includes a pre-grinding process and a finishing grinding process. The pre-grinding process typically includes a rough grinding process (first grinding) and an intermediate grinding process (second grinding).

[0003] For silicon wafers, for identification purposes, barcodes, numbers, markings, etc., are sometimes affixed by irradiating the surface and back of the silicon wafer with a laser (hard laser marking; hereinafter sometimes referred to as "HLM"). HLM application is generally performed after the silicon wafer grinding process and before the polishing process begins. Typically, due to the irradiation by the laser used to apply the HLM, a modified layer is formed on the silicon wafer surface around the HLM. The HLM portion of the silicon wafer itself is not used in the final product, but in the polishing process after HLM application (especially the pre-grinding process), if the modified layer is not properly ground, it may become a bulge, leading to a significant reduction in yield. However, the modified layer is transformed into polycrystalline silicon or similar materials by the laser energy, making it difficult to grind. Therefore, conventional grinding compositions for silicon wafers are insufficient to effectively suppress the occurrence of such bulges.

[0004] Existing technical documents

[0005] Patent documents

[0006] Patent Document 1: International Publication No. 2019 / 189124

[0007] Patent Document 2: Japanese Patent Application Publication No. 2020-021810 Summary of the Invention

[0008] The problem the invention aims to solve

[0009] Patent documents 1 and 2 are cited as examples of technical documents relating to the elimination of HLM periphery bulges (hereinafter also referred to as "bulges"). The aforementioned patent documents propose to eliminate bulges by using specific types of surfactants, but there are still shortcomings in balancing the high grinding rate suitable for the pre-grinding process with the elimination of bulges.

[0010] Therefore, the object of the present invention is to provide a polishing composition for a pre-polishing process of silicon wafers, which can effectively suppress the reduction of polishing rate and eliminate the bulge around the HLM edge.

[0011] Solution for solving the problem

[0012] According to the present invention, a polishing composition is provided for use in a pre-polishing process of silicon wafers. The polishing composition comprises abrasive particles, an alkaline compound, a chelating agent, a surfactant, a nitrogen-containing water-soluble polymer, and water. Furthermore, the weight concentration (B) of the alkaline compound relative to the weight concentration (S) of the surfactant (B / S) is 50 or more. With this polishing composition, it is possible to suppress the decrease in polishing rate and effectively eliminate bulges around the HLM (Highly Molecular Weighted Laminate).

[0013] It should be noted that, in this specification, eliminating the bulge around the HLM means reducing the height from the reference plane around the HLM on the silicon wafer to the highest point of the bulge. The height from the reference plane around the HLM on the silicon wafer to the highest point of the bulge can be measured, for example, by the method described in the embodiments below.

[0014] In a preferred embodiment of the grinding composition disclosed herein, the weight concentration (P) of the nitrogen-containing water-soluble polymer relative to the weight concentration (S) of the surfactant (P / S) is greater than 0.5. This configuration can suppress the reduction in grinding rate and more appropriately eliminate bulges around the HLM periphery.

[0015] In a preferred embodiment of the grinding composition disclosed herein, the surfactant comprises a nonionic surfactant. This configuration can suppress the reduction in grinding rate and more effectively eliminate bulges around the HLM periphery.

[0016] In a preferred embodiment, the aforementioned nonionic surfactant is a polyoxyalkylene alkyl ether. This configuration can suppress the decrease in grinding rate and more effectively eliminate bulges around the HLM periphery.

[0017] In a preferred embodiment of the grinding composition disclosed herein, the abrasive particles comprise silica particles. In grinding using silica particles as abrasive particles, the reduction in grinding rate can be suppressed, and the effect of eliminating HLM periphery bulges can be achieved more effectively. Detailed Implementation

[0018] Abrasive grains

[0019] The grinding composition disclosed herein contains abrasive particles. The material and properties of the abrasive particles are not particularly limited and can be appropriately selected according to the intended use of the grinding composition. Examples of abrasive particles include inorganic particles, organic particles, and organic-inorganic composite particles. Specific examples of inorganic particles include oxide particles such as silica particles, alumina particles, cerium oxide particles, chromium oxide particles, titanium dioxide particles, zirconium oxide particles, magnesium oxide particles, manganese dioxide particles, zinc oxide particles, and iron oxide red particles; nitride particles such as silicon nitride particles and boron nitride particles; carbide particles such as silicon carbide particles and boron carbide particles; diamond particles; and carbonates such as calcium carbonate and barium carbonate. Specific examples of organic particles include polymethyl methacrylate (PMMA) particles or poly(meth)acrylic acid particles, and polyacrylonitrile particles. Here, (meth)acrylic acid means including acrylic acid and methacrylic acid. One type of abrasive particle can be used alone or in combination of two or more types.

[0020] As the aforementioned abrasive grains, inorganic particles are preferred, particularly those formed from oxides of metals or semi-metals. In the technology disclosed herein, silica particles are a preferred example of usable particles. The reasons are as follows: In grinding with a silicon wafer as the grinding target, if silica particles formed from the same elements and oxygen atoms as the grinding target are used as abrasive grains, no metal or semi-metal residues different from silicon are produced after grinding. Therefore, there is no concern about the deterioration of the electrical properties of the silicon wafer due to contamination of the silicon wafer surface or diffusion of metals or semi-metals different from silicon within the grinding target. Furthermore, silicon and silica have similar hardness, so grinding can be performed without causing excessive damage to the silicon wafer surface.

[0021] Specific examples of silica particles include colloidal silica, fumed silica, and precipitated silica. From the viewpoint of minimizing scratches on the surface of the object being polished and achieving a surface with lower haze, colloidal silica and fumed silica are preferred silica particles. Colloidal silica is preferred among these.

[0022] In the technology disclosed herein, the abrasive particles contained in the grinding composition can be in the form of primary particles or in the form of secondary particles formed by the association of multiple primary particles. Furthermore, a mixture of primary and secondary abrasive particles may also be present. In a preferred embodiment, at least a portion of the abrasive particles are contained in the grinding composition in the form of secondary particles.

[0023] The average primary particle size of the abrasive grains (typically silica particles) is not particularly limited, but from the viewpoint of balancing the reduction of grinding rate and the elimination of bulges, it is preferably 5 nm or more, more preferably 10 nm or more, and particularly preferably 20 nm or more. From the viewpoint of obtaining a higher grinding effect, the average primary particle size is preferably 25 nm or more, more preferably 30 nm or more. Abrasive grains with an average primary particle size of 40 nm or more can also be used. Furthermore, from the viewpoint of preventing scratches, the average primary particle size of the abrasive grains is preferably 200 nm or less, more preferably 150 nm or less, for example, 100 nm or less.

[0024] It should be noted that the average primary particle size in this specification refers to the specific surface area (BET value) determined using the BET method, calculated using the formula: Average primary particle size (nm) = 6000 / (True density (g / cm³)). 3 )×BET value (m 2 The particle size (BET particle size) is calculated as (g). The specific surface area mentioned above can be measured, for example, using a surface area measuring device manufactured by Micromeritics, trade name "FlowSorb II 2300".

[0025] The average secondary particle size of the abrasive grains (e.g., silica particles) is not particularly limited, but from the viewpoint of balancing the reduction of grinding rate and the improvement of ridge elimination, it is preferably 15 nm or more, and more preferably 30 nm or more. From the viewpoint of obtaining a higher grinding effect, the average secondary particle size is preferably 50 nm or more. Furthermore, from the viewpoint of preventing scratches, the average secondary particle size of the abrasive grains is appropriately 300 nm or less, preferably 260 nm or less, and more preferably 220 nm or less.

[0026] It should be noted that the secondary average particle size in this specification refers to the particle size (volume average particle size) measured using the dynamic light scattering method. The average secondary particle size of the abrasive particles can be measured using, for example, the "FPAR-1000" manufactured by Otsuka Electric Co., Ltd., or an alternative thereof.

[0027] The shape (outer shape) of abrasive grains can be spherical or non-spherical. Specific examples of non-spherical abrasive grains include peanut-shaped (i.e., the shape of a peanut shell), cocoon-shaped, konpeito-shaped, rugby ball-shaped, etc.

[0028] While not particularly limited, the average length-to-diameter ratio (ARR) of the primary abrasive grains is preferably 1.05 or higher, more preferably 1.1 or higher. Increasing the ARR of the abrasive grains allows for higher grinding rates. Furthermore, from the viewpoint of reducing scratches, the ARR of the abrasive grains is preferably 3.0 or lower, more preferably 2.0 or lower. In several embodiments, the ARR of the abrasive grains may, for example, be 1.5 or lower, 1.4 or lower, or 1.3 or lower.

[0029] The shape (outline) or average aspect ratio of the aforementioned abrasive grains can be determined, for example, by observation using an electron microscope. As a specific step in determining the average aspect ratio, for example, using a scanning electron microscope (SEM), for a specific number (e.g., 200) of abrasive grains with identifiable individual grain shapes, the smallest rectangle circumscribed to each grain image is drawn. Then, for each grain image, the aspect ratio (length / short diameter ratio) is calculated by dividing the length of its longer side (the value of the major diameter) by the length of its shorter side (the value of the minor diameter). The average aspect ratio can be obtained by taking the arithmetic mean of the aspect ratios of the aforementioned specific number of grains.

[0030] The content of abrasive particles in the grinding composition is not particularly limited, but is typically 0.1% by weight or more. From the viewpoint of balancing the reduction of grinding rate and the improvement of ridge elimination, it is preferably 0.2% by weight or more, more preferably 0.5% by weight or more, and even more preferably 1.0% by weight or more. By increasing the content of abrasive particles, a higher grinding rate can be achieved. In addition, the above-mentioned content is usually appropriately 10% by weight or less, preferably 5% by weight or less, more preferably 3% by weight or less or 2% by weight or less (e.g., 1.3% by weight or less).

[0031] <Alkaline compounds>

[0032] The grinding composition disclosed herein contains an alkaline compound. An alkaline compound, as used herein, is a compound that, by being added to the grinding composition, raises the pH of the composition. The alkaline compound can be an organic alkaline compound or an inorganic alkaline compound. One alkaline compound may be used alone or in combination of two or more.

[0033] Examples of organic basic compounds include quaternary ammonium salts such as tetraalkylammonium salts. The anion in these ammonium salts can be, for example, OH-. - F - Cl - ,Br - I - ClO4 - BH4 - HCO3 -Suitable alternatives include quaternary ammonium salts such as choline, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, and tetramethylammonium bicarbonate. Tetramethylammonium hydroxide is preferred.

[0034] Other examples of organic basic compounds include quaternary phosphonium salts such as tetraalkylphosphonium salts. The anion in these phosphonium salts can be, for example, OH-. - F - Cl - ,Br - I - ClO4 - BH4 - HCO3 - Halides and hydroxides such as tetramethylphosphonium, tetraethylphosphonium, tetrapropylphosphonium, and tetrabutylphosphonium are preferred.

[0035] Other examples of basic organic compounds include amines such as methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, monoethanolamine, N-(β-aminoethyl)ethanolamine, hexamethylenediamine, diethylenetriamine, and triethylenetetramine; piperazines such as 1-(2-aminoethyl)piperazine and N-methylpiperazine; azoles such as imidazoles and triazoles; and guanidines.

[0036] Examples of inorganic basic compounds include: ammonia; hydroxides of ammonia, alkali metals, or alkaline earth metals; carbonates of ammonia, alkali metals, or alkaline earth metals; bicarbonates of ammonia, alkali metals, or alkaline earth metals, etc. Specific examples of the aforementioned hydroxides include potassium hydroxide and sodium hydroxide. Specific examples of the aforementioned carbonates or bicarbonates include ammonium bicarbonate, ammonium carbonate, potassium bicarbonate, potassium carbonate, sodium bicarbonate, and sodium carbonate, etc.

[0037] Examples of preferred alkaline compounds include ammonia, potassium hydroxide, sodium hydroxide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, ammonium bicarbonate, ammonium carbonate, potassium bicarbonate, potassium carbonate, sodium bicarbonate, and sodium carbonate. Among these, ammonia, potassium hydroxide, sodium hydroxide, tetramethylammonium hydroxide, and potassium carbonate are preferred. Tetramethylammonium hydroxide and potassium carbonate are even more preferred.

[0038] The content of the alkaline compound in the grinding composition is typically 0.005% by weight or more. From the viewpoint of grinding rate, the above content is preferably 0.01% by weight or more, more preferably 0.05% by weight or more, and even more preferably 0.1% by weight or more. Furthermore, the content of the above-mentioned alkaline compound is typically 1% by weight or less, preferably 0.5% by weight or less, and more preferably 0.3% by weight or less. In grinding compositions used directly as grinding fluids, the above content can, for example, be 0.5% by weight or less, or 0.2% by weight or less.

[0039] <surfactants>

[0040] The grinding composition disclosed herein also contains a surfactant. The weight concentration (B) of the alkaline compound relative to the weight concentration (S) of the surfactant (B / S) is preferably 50 or more. When the B / S ratio is 50 or more, a suitable balance is achieved between the grinding promotion based on the alkaline compound and the grinding surface protection based on the surfactant. Furthermore, by using a nitrogen-containing water-soluble polymer in combination, the nitrogen-containing water-soluble polymer acts on the bulges around the HLM (Highly Molecular Weight Meridian), allowing the surfactant to act efficiently on the bulges. This suppresses the decrease in grinding rate and effectively improves bulge elimination. It should be noted that the above mechanism is based on the inventors' observations of experimental results, and the technology disclosed herein should not be limited to the above mechanism.

[0041] In several embodiments, the B / S ratio is preferably 70 or higher, more preferably 120 or higher, and can be 150 or higher, 200 or higher, 300 or higher, or 400 or higher. Increasing the B / S ratio further enhances the effect of suppressing the decrease in grinding rate and improving the elimination of raised areas. Furthermore, from the viewpoint of surface quality after grinding, in several embodiments, the B / S ratio can be, for example, 5000 or lower, preferably 2000 or lower, more preferably 1200 or lower, 800 or lower, or 600 or lower.

[0042] As surfactants, any of the following can be used: anionic, cationic, nonionic, or amphoteric. Generally, anionic or nonionic surfactants are preferred. From the viewpoint of low foaming properties and ease of pH adjustment, nonionic surfactants are more preferred. Examples include alkylene oxide polymers such as polyethylene glycol, polypropylene glycol, and polybutanediol; polyoxyalkylene oxide derivatives (e.g., polyoxyalkylene adducts) such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene alkylamines, polyoxyethylene fatty acid esters, polyoxyethylene glycerol ether fatty acid esters, and polyoxyethylene sorbitan fatty acid esters; copolymers of various alkylene oxides (e.g., diblock copolymers, triblock copolymers, random copolymers, alternating copolymers); and other nonionic surfactants. Among the above-mentioned surfactants, surfactants containing a polyoxyalkylene structure (a repeating structure of alkylene oxide units, i.e., a polyoxyalkylene alkyl chain, hereinafter also referred to as a "POA chain") are preferred. One surfactant can be used alone or in combination of two or more.

[0043] Examples of the aforementioned oxoalkylene units include oxoethylene units, oxopropylene units, and oxobutylene units. These oxoalkylene units can be repeating units derived from the corresponding epoxides, but are not limited to this. The POA chain of the surfactant may contain one or more oxoalkylene units. In a POA chain containing two or more oxoalkylene units, the content ratio of these oxoalkylene units is not particularly limited. Furthermore, in a POA chain containing two or more oxoalkylene units, these oxoalkylene units can be random copolymers, block copolymers, alternating copolymers, or graft copolymers of the corresponding epoxides. A single surfactant may be used alone, or two or more may be used in combination.

[0044] Specific examples of surfactants include polyoxyalkylene alkyl ethers (e.g., polyoxyethylene alkyl ethers, polyoxypropylene alkyl ethers, polyoxyethylene polyoxypropylene alkyl ethers, polyoxyethylene polyoxybutylene alkyl ethers); polyoxyalkylene alkenyl ethers (e.g., polyoxyethylene oleyl ethers); polyoxyalkylene phenyl ethers (e.g., polyoxyethylene phenyl ethers, polyoxyethylene styrene phenyl ethers, polyoxyethylene octylphenyl ethers, polyoxyethylene nonylphenyl ethers, polyoxyethylene dodecylphenyl ethers, etc.); polyoxyalkylene alkylamines (e.g., polyoxyethylene laurylamine, polyoxyethylene stearylamine, polyoxyethylene oleylamine); and polyoxyalkylene fatty acid esters (e.g., polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene monooleate, polyoxyethylene distearate, etc.). Monoesters or diesters of saturated or unsaturated fatty acids such as oxyethylidene dioleate; polyoxyalkylene sorbitan fatty acid esters (e.g., polyoxyalkylene sorbitan monolaurate, polyoxyalkylene sorbitan monopalmitate, polyoxyalkylene sorbitan monostearate, polyoxyalkylene sorbitan monooleate, polyoxyalkylene sorbitan monooleate, polyoxyalkylene sorbitan trioleate); polyoxyalkylene sorbitols of fatty acids (e.g., polyoxyalkylene sorbitol tetraoleate); block copolymers of ethylene oxide (EO) and propylene oxide (PO) (e.g., diblock copolymers, PEO-PPO-PEO triblock copolymers, PPO-PEO-PPO triblock copolymers, etc.); random copolymers of EO and PO; in addition, polyoxyethylene glycol, polyoxyethylated castor oil, polyoxyethylated hydrogenated castor oil, etc. Among several methods, polyoxyalkylene ethers are preferred as surfactants.

[0045] The number of olefin units in the surfactant, i.e., the molar number of epoxides added, can be selected in a way that appropriately maximizes the effectiveness of the surfactant. There is no particular upper limit to the molar number of epoxides added; for example, it can be 100 or less, preferably 80 or less, and from the viewpoint of suppressing a decrease in grinding rate, preferably 60 or less, more preferably 40 or less, even more preferably 30 or less, and can be 25 or less, or 18 or less (e.g., 14 or less). There is no particular lower limit to the molar number of epoxides added; for example, it can be 3 or more, preferably 5 or more, preferably 7 or more (e.g., 9 or more), and can be 10 or more, 12 or more, or 15 or more (e.g., 20 or more).

[0046] From the viewpoint of suppressing the decrease in grinding rate and appropriately exerting the effect of improving the elimination of bulges, surfactants having POA chains containing at least olefin oxide units are preferred in several embodiments. The percentage of oxyethylidene units (EO number) in the total number of olefin oxide units contained in the surfactant is, for example, 1% or more, preferably 5% or more, more preferably 10% or more, and can be 20% or more, 30% or more, 45% or more, or 55% or more. Alternatively, the olefin oxide units can be 100% oxyethylidene units. When the surfactant combination includes both oxyethylidene units and oxypropylene units, the ratio of the number of oxypropylene units (PO number) to the number of oxyethylidene units (PO / EO) can be, for example, 5.0 or less, preferably 3.0 or less, and more preferably 2.0 or less. In several embodiments, the above ratio (PO / EO) can be, for example, 1.5 or less, 1.0 or less, or 0.8 or less. Furthermore, the aforementioned ratio (PO / EO) can be, for example, 0.1 or higher, 0.2 or higher, 0.4 or higher, 0.6 or higher, 0.9 or higher, or 1.3 or higher.

[0047] When using polyoxyalkylene alkyl ethers as surfactants, the number of carbon atoms in the alkyl group of the alkyl ether is not particularly limited, and can be selected in a way that appropriately maximizes the effectiveness of the surfactant. From the viewpoint of easily exerting surface activity, the number of carbon atoms in the alkyl group is preferably 3 or more, and more preferably 5 or more. It should be noted that, from the viewpoint of surface protection of the object being ground, the number of carbon atoms in the alkyl group is preferably 7 or more, and more preferably 8 or more. In some embodiments, the number of carbon atoms in the alkyl group can be 10 or more, or 12 or more. The number of carbon atoms in the alkyl group can be, for example, 27 or less, 25 or less, or 20 or less. From the viewpoint of surfactant solubility, in some embodiments, the number of carbon atoms in the alkyl group is preferably 18 or less, more preferably 16 or less, and even more preferably 14 or less. The alkyl group can be straight-chain or branched. Specific examples of alkyl groups in the alkyl ether include propyl, butyl, pentyl, hexyl, octyl, 2-ethylhexyl, nonyl, decyl, isodecyl, lauryl, tridecyl, cetyl, stearyl, isostearyl, etc., but are not limited to these.

[0048] As the aforementioned polyoxyalkylene alkyl ethers, those in which the primary carbon of an alkyl group is bonded to the polyoxyalkylene alkyl group via an ether bond (hereinafter also referred to as "polyoxyalkylene primary alkyl ethers") and those in which the secondary carbon of an alkyl group is bonded to the polyoxyalkylene alkyl group via an ether bond (hereinafter also referred to as "polyoxyalkylene secondary alkyl ethers") are preferred. In the aforementioned polyoxyalkylene alkylene primary alkyl ethers, the alkyl group can be straight-chain or branched. In the aforementioned polyoxyalkylene alkylene secondary alkyl ethers, the two alkyl groups bonded to the secondary carbon group can be the same or different from each other. The two alkyl groups bonded to the secondary carbon group can each be independently straight-chain or branched.

[0049] Among several methods, from the viewpoint of improving the elimination of bulges, polyoxyalkylene primary alkyl ethers are preferred as surfactants. The weight percentage of polyoxyalkylene primary alkyl ethers in the surfactant is, for example, 50% by weight or more, 70% by weight or more, 90% by weight or more, or 100% by weight or more. Polyoxyalkylene primary alkyl ethers can be used alone or in combination of two or more.

[0050] In the grinding compositions disclosed herein, the weight-average molecular weight (Mw) of the surfactant is not particularly limited and can be suitably selected within a range that appropriately exerts the effects of the present invention. From the viewpoint of suppressing the decrease in grinding rate, in several embodiments, it is appropriate for the Mw of the surfactant to be less than 4000, preferably 3000 or less, more preferably 2500 or less, further preferably 2000 or less, and may also be 1500 or less. Furthermore, from the viewpoint of surface activity, the Mw of the surfactant is appropriately 200 or more, and from the viewpoint of improving bulge elimination, it is preferably 300 or more (e.g., 350 or more). In several embodiments, the Mw of the surfactant may be 400 or more, 500 or more, 600 or more, or 700 or more.

[0051] It should be noted that, in this specification, the molecular weight Mw used as a surfactant is calculated based on the chemical formula. Furthermore, similar to the nitrogen-containing water-soluble polymers described later, the molecular weight may also be calculated based on water-based gel chromatography (GPC) values ​​(water-based, converted to polyethylene oxide).

[0052] The content of surfactant in the grinding composition is not particularly limited as long as it does not significantly hinder the effects of the present invention. For example, the surfactant content can be 1.0 × 10⁻⁶. -6 From the perspective of improving the elimination of bulges, a concentration of 5.0 × 10⁻⁶ is appropriate, exceeding 5% by weight. -6 More than % by weight, preferably 1.0 × 10⁻⁶. -5 At a weight percentage or higher, it can be 5.0 × 10⁻⁶. -5 More than % by weight, and more preferably 1.0 × 10⁻⁶. -4 The content of the surfactant is 0.5% by weight or more. Furthermore, the content of the surfactant may be, for example, 0.5% by weight or less, but from the viewpoint of suppressing a decrease in the grinding rate, it is suitable to be 0.25% by weight or less, preferably 0.1% by weight or less, more preferably 0.05% by weight or less, and may also be 0.01% by weight or less. It should be noted that when the grinding composition disclosed herein contains two or more surfactants, the above-mentioned content refers to the total content of these surfactants. The above-mentioned surfactant content is preferably adopted when the grinding composition is used in the form of a grinding fluid.

[0053] <Nitrogen-containing water-soluble polymers>

[0054] The grinding composition disclosed herein also contains a nitrogen-containing water-soluble polymer. There is no particular limitation on the nitrogen-containing water-soluble polymer, as long as it is a water-soluble polymer having one or more nitrogen atoms (N) within its molecule; it can be a homopolymer or a copolymer. Such copolymers can be, for example, diblock copolymers, triblock copolymers, random copolymers, alternating copolymers, etc. One nitrogen-containing water-soluble polymer can be used alone, or two or more can be used in combination.

[0055] The aforementioned nitrogen-containing water-soluble polymers can be, for example, water-soluble polymers whose main chain contains nitrogen atoms and whose side chains contain nitrogen atoms. Specific examples of water-soluble polymers whose main chain contains nitrogen atoms include homopolymers and copolymers of alkylene imine type monomers (e.g., ethyleneimine, propyleneimine, N-acetyl ethyleneimine, N-propionyl ethyleneimine, N-acetyl propyleneimine, N-formyl ethyleneimine).

[0056] Specific examples of water-soluble polymers whose side chains contain nitrogen atoms include N-vinyl polymers and N-(meth)acryloyl polymers. Specific examples of N-vinyl polymers include polymers containing repeating units derived from monomers having nitrogen-containing heterocycles (e.g., lactam rings). Examples of such polymers include homopolymers and copolymers of N-vinyl lactam monomers (e.g., copolymers with a copolymerization ratio of N-vinyl lactam monomers exceeding 50% by weight), and homopolymers and copolymers of N-vinyl chain amides (e.g., copolymers with a copolymerization ratio of N-vinyl chain amides exceeding 50% by weight).

[0057] Specific examples of N-vinyllactam type monomers (i.e., compounds having a lactam structure and N-vinyl groups within a single molecule) include N-ethylenpyrrolidone (VP), N-vinylpiperidone, N-vinylmorpholine, N-vinylcaprolactam (VC), N-vinyl-1,3-oxazin-2-one, and N-vinyl-3,5-morpholinidone. Specific examples of polymers containing N-vinyllactam type monomer units include polyvinylpyrrolidone, polyvinylcaprolactam, random copolymers of VP and VC, random copolymers of one or both of VP and VC with other vinyl monomers (e.g., acrylic monomers, vinyl ester monomers, etc.), block copolymers containing polymer chains containing one or both of VP and VC, alternating copolymers, or random copolymers. Specific examples of N-vinyl chain amides include N-vinylacetamide, N-vinylpropionamide, and N-vinylbutyramide.

[0058] Specific examples of N-(meth)acrylamide polymers include homopolymers and copolymers of N-(meth)acrylamide polymers (typically copolymers in which the copolymerization ratio of N-(meth)acrylamide monomers exceeds 50% by weight). Examples of N-(meth)acrylamide monomers include chain amides having N-(meth)acrylamide groups and cyclic amides having N-(meth)acrylamide groups.

[0059] Examples of chain amides having an N-(meth)acryloyl group include (meth)acrylamide; N-alkyl (meth)acrylamides such as N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and N-n-butyl(meth)acrylamide; and N,N-dialkyl (meth)acrylamides such as N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, and N,N-di(n-butyl)(meth)acrylamide. Examples of polymers containing chain amides having an N-(meth)acryloyl group as monomer units include homopolymers of N-isopropylacrylamide and copolymers of N-isopropylacrylamide (e.g., copolymers in which the copolymerization ratio of N-isopropylacrylamide exceeds 50% by weight).

[0060] Examples of cyclic amides having an N-(meth)acryloyl group include N-acryloylmorpholine, N-acryloylthiomorpholine, N-acryloylpiperidine, N-acryloyltetrahydropyrrole, N-methacryloylmorpholine, N-methacryloylpiperidine, and N-methacryloyltetrahydropyrrole. Examples of polymers containing cyclic amides having an N-(meth)acryloyl group as monomer units include acryloylmorpholine polymers (PACMO). Typical examples of acryloylmorpholine polymers include homopolymers of N-acryloylmorpholine (ACMO) and copolymers of ACMO (e.g., copolymers with a copolymerization ratio of ACMO exceeding 50% by weight). In acryloylmorpholine polymers, the molar percentage of ACMO units relative to the total molar percentage of repeating units is typically 50% or more, appropriately 80% (e.g., 90% or more, typically 95% or more). All repeating units of water-soluble polymers can also be substantially composed of ACMO units.

[0061] The weight-average molecular weight (Mw) of the aforementioned nitrogen-containing water-soluble polymers is not particularly limited. For example, the Mw of a nitrogen-containing water-soluble polymer is 5 × 10⁻⁶. 3 From the perspective of improving the elimination of bulges, the preferred value is 1×10. 4 The above is preferred, and more preferably is 1.2 × 10⁻⁶. 4 The above is further preferably 1.5×104 That's all. Furthermore, the Mw of nitrogen-containing water-soluble polymers can, for example, be 80 × 10⁻⁶. 4 From the perspectives of the filterability of the grinding composition and the cleanability of the object being ground, a value of 60×10 is appropriate. 4 The following is preferred: 40×10 4 From the viewpoint of suppressing the decrease in grinding rate, among several methods, the Mw of the nitrogen-containing water-soluble polymer is preferably 25 × 10⁻⁶. 4 Hereinafter, 15×10 is preferred. 4 The following can be 9×10 4 The following can be 6×10 4 The following can also be 3×10 4 the following.

[0062] It should be noted that, in this specification, the molecular weight Mw, referring to the nitrogen-containing water-soluble polymer, can be calculated using a water-based gel chromatography (GPC) value (water is converted to polyethylene oxide). The GPC measuring apparatus can be the HLC-8320GPC manufactured by Tosoh Corporation. The determination can be performed under the conditions described below. The examples described later also employ the same method.

[0063] [GPC Measurement Conditions]

[0064] Sample concentration: 0.1% by weight

[0065] Column: TSKgel GMPWXL

[0066] Detector: Differential refractometer

[0067] Eluent: 100mM sodium nitrate aqueous solution / acetonitrile = 10-8 / 0-2

[0068] Flow rate: 1 mL / min

[0069] Measurement temperature: 40℃

[0070] Sample injection volume: 200 μL

[0071] The content of the nitrogen-containing water-soluble polymer in the grinding composition is not particularly limited as long as it does not significantly hinder the effects of the present invention. For example, the content of the nitrogen-containing water-soluble polymer can be 1.0 × 10⁻⁶. -6 From the perspective of improving the elimination of bulges, a concentration of 5.0 × 10⁻⁶ is appropriate, exceeding 5% by weight. -6 More than % by weight, preferably 1.0 × 10⁻⁶. -5 More than 5.0 × 10 by weight, preferably 5.0 × 10 -5 More than % by weight, more preferably 1.0 × 10⁻⁶. -4The content is % by weight or more. Furthermore, the content of the nitrogen-containing water-soluble polymer can be, for example, 0.5% by weight or less, and from the viewpoint of suppressing a decrease in the grinding rate, appropriately 0.25% by weight or less, preferably 0.1% by weight or less, more preferably 0.05% by weight or less, and can be 0.01% by weight or less, or even 0.001% by weight or less. It should be noted that when the grinding composition disclosed herein contains two or more nitrogen-containing water-soluble polymers, the above-mentioned content refers to the total content of these nitrogen-containing water-soluble polymers. The above-mentioned content of the nitrogen-containing water-soluble polymer is preferably adopted, for example, when the grinding composition is used in the form of a grinding liquid.

[0072] The weight concentration (P) of the nitrogen-containing water-soluble polymer in the grinding composition relative to the weight concentration (S) of the surfactant (P / S) is not particularly limited as long as it does not significantly impair the technical effects disclosed herein. Typically, the P / S ratio is 0.1 or more, preferably 0.2 or more, more preferably 0.5 or more (above 0.5), and can be 1.0 or more (above 1.0), or 2.0 or more. By increasing the P / S ratio, it is preferable to achieve both suppression of grinding rate reduction and improved ridge elimination. Furthermore, the P / S ratio can, for example, be 10 or less, preferably 8.0 or less, more preferably 6.0 or less, 5.0 or less, or 4.0 or less.

[0073] Chelating agents

[0074] The grinding composition disclosed herein contains a chelating agent. The chelating agent forms a complex ion with any metallic impurities that may be present in the grinding composition, thereby capturing them. This inhibits contamination of the workpiece due to metallic impurities. The chelating agent can be used alone or in combination of two or more.

[0075] Examples of chelating agents include aminocarboxylic acid chelating agents, organophosphonic acid chelating agents, and organosulfonic acid chelating agents. Examples of aminocarboxylic acid chelating agents include ethylenediaminetetraacetic acid (EDTA), sodium EDTA, aziridine triacetic acid, sodium aziridine triacetic acid, ammonium aziridine triacetic acid, hydroxyethyl EDTA, sodium hydroxyethyl EDTA, diethylenetriaminepentaacetic acid, sodium diethylenetriaminepentaacetic acid, triethylenetetraminehexaacetic acid, and sodium triethylenetetraminehexaacetic acid. Examples of organophosphonic acid chelating agents include 2-aminoethylphosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, aminotris(methylenephosphonic acid), ethylenediaminetetra(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), ethane-1,1-diphosphonic acid, ethane-1,1,2-triphosphonic acid, ethane-1-hydroxy-1,1-diphosphonic acid, ethane-1-hydroxy-1,1,2-triphosphonic acid, ethane-1,2-dicarboxy-1,2-diphosphonic acid, methanehydroxyphosphonic acid, 2-phosphonobutane-1,2-dicarboxylic acid, 1-phosphonobutane-2,3,4-tricarboxylic acid, and α-methylphosphonosuccinic acid. Examples of organosulfonic acid chelating agents include ethylenediaminetetramethylenesulfonic acid. Organophosphonic acid chelating agents or organosulfonic acid chelating agents are more preferred among these, with ethylenediaminetetra(methylenephosphonic acid) being a preferred example.

[0076] The content of the chelating agent in the grinding composition is typically suitable to be 0.0001% by weight or more. Preferably, the content is 0.0005% by weight or more, more preferably 0.001% by weight or more. Furthermore, the content of the chelating agent is typically suitable to be 0.05% by weight or less, preferably 0.01% by weight or less, more preferably 0.008% by weight or less, and even more preferably 0.005% by weight or less.

[0077] <Water>

[0078] The grinding composition disclosed herein contains water. Suitable water types include ion-exchanged water (deionized water), pure water, ultrapure water, and distilled water. To minimize interference with the effects of other components in the grinding composition, the total content of transition metal ions in the water used is preferably 100 ppb or less. For example, impurity ions can be removed using ion exchange resins, foreign matter can be removed using filters, and the purity of the water can be improved using distillation.

[0079] <Preparation of Grinding Compositions>

[0080] The method for manufacturing the grinding composition disclosed herein is not particularly limited. For example, well-known mixing devices such as blade mixers, ultrasonic dispersers, and homogenizers can be used to mix the components contained in the grinding composition. The manner in which these components are mixed is not particularly limited. For example, all components can be mixed at once, or they can be mixed in a suitably predetermined order.

[0081] The grinding composition disclosed herein can be a single-component type or a multi-component type, such as a two-component type. For example, it can be configured to mix liquid A, which contains a portion of the components of the grinding composition, with liquid B, which contains the remaining components, and then use it for grinding an object.

[0082] <Grinding Fluid>

[0083] The grinding compositions disclosed herein are typically supplied to the object to be ground in the form of a grinding slurry containing the grinding composition. The grinding slurry is then used for grinding the object. The grinding slurry can be, for example, prepared by diluting any of the grinding compositions disclosed herein. Dilution here typically refers to water-based dilution. Alternatively, the grinding composition can be used directly as a grinding slurry. Other examples of grinding slurries containing the grinding compositions disclosed herein include grinding slurries prepared by adjusting the pH of the composition.

[0084] The pH of the grinding slurry is 8.0 or higher, preferably 8.5 or higher, more preferably 9.0 or higher, even more preferably 9.5 or higher, and particularly preferably 10.0 or higher, for example, 10.5 or higher. Increasing the pH of the grinding slurry tends to increase the grinding rate. The upper limit of the pH of the grinding slurry is not particularly limited, but it can be 12.0 or lower, preferably 11.8 or lower, and more preferably 11.5 or lower.

[0085] <Concentrated Solution>

[0086] The grinding composition disclosed herein can also be in a concentrated form before being supplied to the object being ground. From the viewpoints of convenience in manufacturing, distribution, and storage, as well as cost reduction, such a concentrated form of the grinding composition is advantageous. The concentration ratio is not particularly limited, but is, for example, approximately 2 to 80 times the volume, preferably approximately 5 to 60 times, and can be approximately 15 to 40 times, or approximately 25 to 40 times.

[0087] Such a concentrated grinding composition can be diluted at a desired time to prepare a grinding slurry, and then used to supply the grinding slurry to the object being ground. Typically, this dilution can be performed by adding water to the concentrated composition and mixing. Furthermore, in the multi-component grinding compositions described later, a portion of the components can be diluted and mixed with other agents to prepare a grinding slurry, or the mixture of multiple components can be diluted to prepare a grinding slurry.

[0088] The abrasive content in the above-mentioned concentrate can be, for example, 50% by weight or less. From the viewpoint of the stability and filterability of the grinding composition, the above content is generally preferably 45% by weight or less, more preferably 40% by weight or less. The stability of the grinding composition here can be exemplified by, for example, the dispersion stability of the abrasive particles. Furthermore, from the viewpoint of convenience in manufacturing, distribution, and storage, as well as cost reduction, the abrasive content can be, for example, 1.0% by weight or more, preferably 3.0% by weight or more, more preferably 5.0% by weight or more, and even more preferably 7.0% by weight or more.

[0089] The content of alkaline compounds in the above-mentioned concentrate is typically 0.03% by weight or more. Preferably, it is 0.15% by weight or more, more preferably 0.3% by weight or more, and even more preferably 1% by weight or more. Furthermore, the content of alkaline compounds is typically 15% by weight or less, preferably 10% by weight or less, more preferably 6% by weight or less, and can be 4% by weight or less, or 3% by weight or less.

[0090] The surfactant content in the above-mentioned concentrate can be, for example, 0.0001% by weight or more, preferably 0.001% by weight or more, more preferably 0.005% by weight or more, and even more preferably 0.01% by weight or more. Furthermore, the surfactant content is generally suitable to be 1% by weight or less, preferably 0.5% by weight or less, and can be 0.1% by weight or less, 0.05% by weight or less, or 0.03% by weight or less.

[0091] The content of nitrogen-containing water-soluble polymers in the above-mentioned concentrate can be, for example, 0.0001% by weight or more, preferably 0.001% by weight or more, more preferably 0.005% by weight or more, and even more preferably 0.01% by weight or more. Furthermore, the content of the above-mentioned nitrogen-containing water-soluble polymers is generally suitable to be 1% by weight or less, preferably 0.5% by weight or less, and can be 0.1% by weight or less, 0.05% by weight or less, or 0.03% by weight or less.

[0092] The content of the chelating agent in the above-mentioned concentrate is generally suitable to be 0.003% by weight or more. Preferably, the content is 0.005% by weight or more, more preferably 0.01% by weight or more, even more preferably 0.03% by weight or more, and particularly preferably 0.05% by weight or more. Furthermore, the content of the chelating agent is generally suitable to be 1.5% by weight or less, preferably 1% by weight or less, more preferably 0.5% by weight or less, even more preferably 0.3% by weight or less, and particularly preferably 0.1% by weight or less.

[0093] <Applications>

[0094] The abrasive compositions disclosed herein are preferably used for abrasive objects having surfaces formed of silicon. The techniques disclosed herein include, for example, abrasive compositions containing silica particles as abrasive grains, which are particularly suitable for abrasive compositions where the abrasive object is silicon. Typically, the abrasive composition contains only silica particles as abrasive grains.

[0095] The shape of the object to be ground is not particularly limited. The grinding composition disclosed herein can be preferably applied, for example, to a flat object to be ground, such as a plate or polyhedron, or to the end of the object to be ground. It can be preferably applied, for example, to the grinding of wafer edges.

[0096] <Grinding Method>

[0097] The polishing composition disclosed herein is used as a pre-polishing composition for polishing single-crystal or polycrystalline silicon wafers. Typically, the silicon wafer has a surface formed of silicon. A typical example of the silicon wafer is a single-crystal silicon wafer, such as a single-crystal silicon wafer obtained by slicing a single-crystal silicon ingot. A preferred embodiment of a method for polishing a target object using the polishing composition disclosed herein will be described below.

[0098] That is, a grinding slurry (slurry) comprising any of the grinding compositions disclosed herein is prepared. The preparation of the grinding slurry may include steps such as adjusting the concentration of the grinding composition to prepare the slurry. Dilution can be cited as an example of concentration adjustment. Alternatively, the grinding composition may be used directly as the grinding slurry. Furthermore, in the case of a multi-component grinding composition, the preparation of the grinding slurry may include steps such as mixing the components, diluting one or more components before mixing, and diluting the mixture after mixing.

[0099] Next, the polishing slurry is supplied to the object to be polished, and polishing is performed using conventional methods. For example, in the case of a first polishing step (initial pre-polishing step) of the object to be polished, the object to be polished after the grinding process is placed in a conventional polishing apparatus. In the first polishing step, typically double-sided polishing is performed. Polishing slurry is supplied to the surface of the object to be polished through the polishing pad of the polishing apparatus. Typically, the polishing slurry is continuously supplied, and the polishing pad is pressed against the surface of the object to be polished, causing the two to move relative to each other (e.g., rotate). Afterwards, a second polishing step (second pre-polishing step) is performed as needed, and finally a finishing polishing step is performed to complete the polishing of the object to be polished. In the second polishing step, typically single-sided polishing is performed.

[0100] It should be noted that the abrasive pad used in the abrasive process using the abrasive composition disclosed herein is not particularly limited. For example, any type of abrasive pad, such as non-woven fabric, suede, polyurethane, containing abrasive particles, or not containing abrasive particles, can be used.

[0101] According to this specification, a method for manufacturing an abrasive is provided, including a step of grinding a workpiece using the abrasive composition disclosed herein. The method for manufacturing an abrasive disclosed herein may further include a step of performing a final polishing on the workpiece after the grinding step using the aforementioned abrasive composition. The final polishing step here refers to the last polishing step in the manufacturing process of the workpiece, that is, a step after which no further polishing is performed. The aforementioned final polishing step may be performed using the abrasive composition disclosed herein, or other abrasive compositions.

[0102] In a preferred embodiment, the polishing process using the above-described polishing composition is a polishing process upstream of the final polishing. It is preferably applied as a pre-polishing step after the grinding process. For example, it is preferably used in a double-sided polishing process (typically a single polishing step) after the grinding process, or in an initial single-sided polishing process (typically an initial second polishing step) on a substrate that has undergone the double-sided polishing process. For both the double-sided polishing process and the initial single-sided polishing process, a higher polishing rate is required compared to the final polishing. Therefore, the polishing composition disclosed herein is suitable for use in polishing at least one (preferably both) of the double-sided polishing process and the initial single-sided polishing process as the object to be polished.

[0103] It should be noted that the above-described grinding composition can be used in a manner that discards it once used in grinding (so-called "overflow"), or it can be recycled and reused. As an example of a method for recycling the grinding composition, one can cite a method of recovering the used grinding composition discharged from the grinding apparatus into a tank and then supplying the recovered grinding composition back to the grinding apparatus. Compared to the case of using it in an overflow manner, recycling the grinding composition reduces the amount of used grinding composition that is treated as waste liquid, thereby reducing the environmental burden. Furthermore, the reduced amount of grinding composition used helps to control costs. When recycling the grinding composition disclosed herein, new components, components that decrease due to use, or components that are desired to be added can be added to the grinding composition in use at any time.

[0104] Example

[0105] The following describes several embodiments of the present invention, but it is not intended to limit the invention to those embodiments. It should be noted that, unless otherwise specified, "%" in the following description refers to weight.

[0106] <Preparation of Grinding Compositions>

[0107] (Examples 1-6)

[0108] A concentrated solution of a grinding composition was prepared by mixing abrasive particles, a surfactant, an alkaline compound, a chelating agent, a nitrogen-containing water-soluble polymer, and deionized water. Silica particles (average primary particle size 55 nm) were used as the abrasive particles. Surfactants A through F, having the structures shown in Table 1, were used as surfactants. It should be noted that in Table 1, "EO number" represents the molar number of ethylene oxide addition, "PO number" represents the molar number of propylene oxide addition, and "carbon number" represents the carbon number of the alkyl group. Furthermore, in the "carbon chain" column, primary carbons of the alkyl group bonded to the polyoxyalkylene group via ether bonds are indicated as "straight chain," and secondary carbons of the alkyl group bonded to the polyoxyalkylene group via ether bonds are indicated as "branched chain." The molecular weights of surfactants A through H are shown in the "molecular weight" column of Table 1. Tetramethylammonium hydroxide (hereinafter referred to as "TMAH") and potassium carbonate (hereinafter referred to as "K2CO3") were used as the alkaline compounds. Ethylenediaminetetra(methylenephosphonic acid) (hereinafter referred to as "EDTPO") is used as a chelating agent. As a nitrogen-containing water-soluble polymer, a Mw of 1.7 × 10⁻⁶ is used. 4 The composition contains polyvinylpyrrolidone (hereinafter referred to as "PVP"). The concentrate of the grinding composition contains 33% abrasive particles, 0.007% surfactant, 2.3% TMAH, 1.1% K2CO3, 0.08% EDTPO, and 0.014% PVP. The weight concentration (B) of the alkaline compound relative to the weight concentration (S) of the surfactant is B / S, which is 486.

[0109] (Comparative Example 1)

[0110] Except for the absence of surfactant, the concentrate of the grinding composition in this example was prepared in the same manner as in Example 1.

[0111] (Comparative Example 2)

[0112] Except for the absence of PVP, the concentrate of the grinding composition in this example was prepared in the same manner as in Example 1.

[0113] (Comparative Example 3)

[0114] Except for the absence of surfactants and PVP, the concentrate of the grinding composition in this example was prepared in the same manner as in Example 1.

[0115] Evaluation of the grinding rate of silicon

[0116] A polishing slurry, prepared by diluting the concentrate of each polishing composition 30 times with water, was used to polish silicon wafers to evaluate the polishing rate and bump removal properties of silicon. A 100mm diameter silicon single-crystal wafer (conductivity: P-type, crystal orientation: ...) that had undergone polishing and etching was used as the polishing material. <100> Resistivity: ≥1Ω·cm and <100Ω·cm.

[0117] (a) Change in wafer thickness before and after grinding [cm] = Difference in weight of silicon wafer before and after grinding [g] / Density of silicon [g / cm³] 3 ](=2.33g / cm 3 ) / Area of ​​grinding object [cm 2 ]

[0118] (b) Grinding rate [μm / min] = Change in wafer thickness before and after grinding [cm] × 10 4 Grinding time [minutes]

[0119] (Grinding conditions)

[0120] Grinding device: Single-sided grinding device manufactured by ENGIS Corporation of Japan, model "EJ-380IN"

[0121] Grinding pressure: 12 kPa

[0122] Plate rotation speed: +50 rpm (clockwise rotation is considered positive rotation. The same applies below).

[0123] Indenter speed: +45 rpm

[0124] Abrasive pad: Manufactured by Nnitta DuPont, trade name "SUBA800"

[0125] Slurry supply rate: 100 mL / min (overflow allowed)

[0126] Maintain grinding environment temperature: 25℃

[0127] Grinding margin: 4μm

[0128] <Evaluation of Elevation Elimination>

[0129] For the polished silicon wafer, the surface shape of the area containing the HLM (High Molecular Mass) was measured using a probe-type surface roughness shape measuring machine (SURFCOM 1500DX, Tokyo Seimitsu Co., Ltd.), and the height from the reference surface around the HLM to the highest point of the bulge was measured. The greater the bulge height, the less effective the bulge elimination is. The results are shown in the "Bulge Height" column of Table 1.

[0130] [Table 1]

[0131] Table 1

[0132]

[0133] As shown in Table 1, based on the grinding compositions of Examples 1 to 6 which contain a nitrogen-containing water-soluble polymer and a surfactant, it can be confirmed that the grinding rate is maintained at the same level as that of the grinding compositions of Comparative Examples 1 and 2 which do not contain either a nitrogen-containing water-soluble polymer or a surfactant, but the bulge elimination is significantly improved.

[0134] Compared with Examples 4 to 6, Examples 1 to 3 tend to have a higher tendency to eliminate bulges.

[0135] Furthermore, as can be seen from the comparison between Comparative Example 3 and Comparative Example 2, the grinding composition not containing nitrogen-containing water-soluble polymers showed a slight decrease in grinding speed when surfactants were added, and no improvement in bulge elimination was observed. In contrast, as can be seen from the comparison between Comparative Example 1 and Example 1, the grinding composition containing nitrogen-containing water-soluble polymers, by further combining it with surfactants, maintained the grinding speed while significantly improving bulge elimination.

[0136] The specific examples of the present invention have been described in detail above, but these are merely illustrative and do not limit the scope of the claims. The technology described in the claims includes various modifications and alterations to the specific examples described above.

Claims

1. The polishing composition is used for pre-polishing silicon wafers with hard laser markings formed on them. The grinding composition is formed from abrasive particles, an alkaline compound, a chelating agent, a surfactant, a nitrogen-containing water-soluble polymer, and water. The alkaline compound is one or more selected from the group consisting of quaternary ammonium salts, quaternary phosphonium salts, amines, piperazines, azoles, guanidines, ammonia, hydroxides of ammonia, alkali metals or alkaline earth metals, carbonates of ammonia, alkali metals or alkaline earth metals, and bicarbonates of ammonia, alkali metals or alkaline earth metals. The surfactant has a weight-average molecular weight of less than 4000, and the nitrogen-containing water-soluble polymer has a weight-average molecular weight of more than 5000. The surfactant has a weight concentration S exceeding 1.0 × 10⁻⁶. -4 weight%, The ratio of the weight concentration B of the alkaline compound to the weight concentration S of the surfactant, i.e., B / S, is 50 or more.

2. The use according to claim 1, wherein, The ratio of the weight concentration P of the nitrogen-containing water-soluble polymer to the weight concentration S of the surfactant, i.e., P / S is greater than 0.

5.

3. The use according to claim 1 or 2, wherein, The surfactants include nonionic surfactants.

4. The use according to claim 3, wherein, The nonionic surfactant is a polyoxyalkylene ether.

5. The use according to claim 1 or 2, wherein, The abrasive particles comprise silicon dioxide particles.

6. The use of a concentrate of the polishing composition according to any one of claims 1 to 5 for pre-polishing a silicon wafer with hard laser markings.

Citation Information

Patent Citations

  • Polishing composition, method of manufacturing the same, and polishing method using polishing composition

    JP2020021810A

  • Ceramic package and piezoelectric device

    JP2021005836A

  • Polishing composition

    WO2019189124A1

  • Polishing composition and polishing method

    CN101130668A

  • Polishing composition and polishing composition set

    CN109673157A